The Regulatory Status Adopted by Lymph Node Dendritic Cells and T Cells During Healthy Aging Is Maintained During Cancer and May Contribute to Reduced Responses to Immunotherapy - Gardner, Joanne K.; Jackaman, Connie; Mamotte, Cyril D. S.; Nelson, Delia J. (Frontiers in Medicine, 2018)
Ageing is associated with an increased incidence of cancer. One contributing factor could be modulation of immune cells responsible for anti-tumour responses, such as dendritic cells (DCs) and T cells. These immunological changes may also impact the efficacy of cancer immunotherapies in the elderly. The effects of healthy ageing on DCs and T cells, and their impact on anti-mesothelioma immune responses, had not been reported. This study examined DCs and T cells in young (2-5 months; equivalent to 16-26 human years) and elderly (20-24 months; equivalent to 60-70 human years) healthy and mesothelioma-bearing C57BL/6J mice. During healthy ageing, elderly lymph nodes adopted a regulatory profile, characterized by: (i) increased plasmacytoid DCs, (ii) increased expression of the adenosine-producing enzyme CD73 on CD11c+ cells, and (iii) increased expression of multiple regulatory markers (including CD73, the adenosine A2B receptor, CTLA-4, PD-1, ICOS, LAG-3, and IL-10) on CD8+ and CD4+ T cells, compared to lymph nodes from young mice. Although mesotheliomas grew faster in elderly mice, the increased regulatory status observed in healthy elderly lymph node DCs and T cells was not further exacerbated. However, elderly tumour-bearing mice demonstrated reduced MHC-I, MHC-II and CD80 on CD11c+ cells, and decreased IFN-γ by CD8+ and CD4+ T cells within tumours, compared to young counterparts, implying loss of function. An agonist CD40 antibody based immunotherapy was less efficient at promoting tumour regression in elderly mice, which may be due to: (i) failure of elderly CD8+ T cells to up-regulate perforin, and (ii) increased expression of multiple regulatory markers on CD11c+ cells and T cells in elderly tumour-draining lymph nodes (including CD73, PD-1, ICOS, LAG-3 and TGF-β). Our findings suggest that checkpoint blockade may improve responses to immunotherapy in elderly hosts with mesothelioma, and warrants further investigation.